Analysis of Virtual World Elements with Emphasis on Property Rights - Shariat Kermani , Aref; Sabahi Garaghani, Moein; Salari, Yaser (Legal Studies in Digital Age, 2025)
In this research, a descriptive-analytical method has been employed to analyze the elements of the virtual world with an emphasis on property rights. The technological development of information and communication technology has brought numerous innovations that have not only optimized our tasks and activities but also enhanced human capacity to expand social relations across borders and in the international arena in this globalized and interconnected world. With millions of online players, persistent and durable computer-generated spaces and environments, known as virtual worlds, play a highly significant and effective role. On the one hand, virtual worlds are used for recreational and entertainment purposes; on the other hand, they can serve as a platform and venue for social interactions and educational or instructional goals, as exemplified by Second Life. In these virtual worlds, users are often represented through symbols and graphical images known as avatars, which are not only used for interaction with other users but also for engagement with virtual objects (such as virtual houses, virtual helmets, virtual clothing, etc.), which can be exchanged and transferred among users within the same virtual world. The Romano-Germanic legal system includes countries with civil law traditions. Accordingly, this codified law is characterized by a coherent, highly structured, and systematic framework. Moreover, this legal tradition, without reference to detailed descriptions, relies on general and abstract principles. Additionally, the creation of new property rights through judicial interpretation is not feasible, as the civil law system renders such possibilities highly restrictive and limited, although the degree of rigidity and strictness varies among countries.